PERAN ORANG TUA DALAM MEMBENTUK AKHLAK REMAJA PADA ERA DIGITALISASI DI DESA KABAR KECAMATAN SAKRA KABUPATEN LOMBOK TIMUR - Paesal Aditiya Azzikrol Hakim; Mukhlis; Zahraini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the role of parents in shaping adolescent morality in the digital era and analyze its impact in Kabar Village, Sakra District, East Lombok Regency. The study employed a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. Data analysis was conducted through the stages of data collection, data reduction, data presentation, and conclusion drawing. Data validity was tested using source and technique triangulation. The results indicate that parents play a role as educators, guides, supervisors, role models, motivators, and protectors in shaping adolescent morality. Positive impacts are seen in increased discipline in studying, performing religious duties, and controlling gadget use. However, impolite behavior in communication, low direct social interaction, and a tendency towards excessive gadget use are still found. Therefore, the active, consistent, and adaptive role of parents in responding to technological developments is crucial in shaping adolescent morality in the digital era.